دراسة مقطعية لتقصي المعلومات المتوفرة حول كيفية اختيار واستخدام وتعقيم ونبذ السنابل لدى أطباء الأسنان في منطقة الساحل السوري - معروف, علي (Latakia University Journal -Medical Sciences Series, 2017)
الهدف : تهدف الدراسة إلى تقييم مستوى المعرفة والثقافة المتوفرة لدى أطباء الأسنان الممارسين حول السنابل من حيث استعمالها تعقيمها و نبذها. المواد وطرائق البحث: تم تحضير استبيان مؤلف من مجموعة من الأسئلة حول السنابل وكيفية استعمالها و تعقيمها و التخلص منها بالإضافة لمعلومات حول الأطباء المستبينين لتحديد علاقة المعلومات العلمية بخبرة الأطباء واختصاصهم، وزع الاستبيان على مجموعه من أطباء الأسنان في الساحل السوري، تم اختيارهم بطريقة عشوائية. N =100)) تقريبا و خلال فترة شهرين فقط، وبعد استعادة الاستبيان من الأطباء، تم تقييم الإجابات المختلفة للأطباء من خلال جدولة الإجابات و من ثم تحليلها إحصائياً. النتائج : بلغت نسبة الأستجابة للأستبيان 76% و قد أظهرت نتائج الدراسة الحالية عدم وجود فرق بين الأطباء المختصين وغير المختصين من حيث مستوى المعلومات المتوفرة حول السنابل واستخدامها, كما لم يكن هناك فرق بين الذكور و الإناث من حيث مستوى المعلومات أيضا حيث (P˃0.05). ومن جهة أخرى تبين وجود علاقة عكسية بين العمر و مستوى المعلومات (P˂0.05). كما تبين أن 52 % فقط من أطباء الأسنان قد استطاعوا تحديد سنبلة إنهاء الكمبوزت المناسبة. الخلاصة : إنَ مستوى المعلومات لدى أطباء الأسنان في الساحل السوري تعتبر مقبولة إلى حد ما و بالرغم من ذلك فهناك حاجة ملحة لزيادة ثقافة أطباء الأسنان حول السنابل و استعمالها و تعقيمها أيضا. The Aim: To evaluate practioner’s knowledge on dental bur selection, its usage, sterilization procedures undertaken and the method of disposal of dental burs. Materials and Methods: A Questionnaire Performa was prepared about dental burs how to use ,sterilized and disposed of them. in addition to information about doctors to determine the relationship between scientific information of doctors with their experience and Specialty. questionnaire was distributed on a group of dentists in the Syrian coast were chosen at random( N = 100) and during the period of almost two months only ,and then the answers analyzed statistically.Results: The response rate was 76%. However, the results of the current study showed that there was no difference between specialists and non-specialists in the level of information available about the burs and use it, as there was no difference between males and females in the level of information On the other hand, the result showed an inverse relationship between age and the level of information (P˂0.05). only 52% of the dentists were able to determine the appropriate composite finishing bur.Conclusion: The level of the information of dentists in the Syrian coast was considered acceptable Nevertheless, there is an urgent need to increase the wright information of dentists around the burs and their use and also their sterilize.